Drainage dynamics of thin liquid foam films containing soft PNiPAM microgels: influence of the cross-linking density and concentration. Issue 1 (25th July 2016) - Keal, L.; Lapeyre, V.; Ravaine, V.; Schmitt, V.; Monteux, C.
Abstract : We investigate the drainage dynamics of thin liquid foam films containing PNiPAM microgel suspensions with two cross-linking densities (1.5 and 5 mol% BIS) and at two microgel concentrations (0.1 and 1% wt). Abstract : We investigate the drainage dynamics of thin liquid foam films containing PNiPAM microgel suspensions with two cross-linking densities (1.5 and 5 mol% BIS) and at two microgel concentrations (0.1 and 1% wt). For this purpose, we use a thin-film pressure balance apparatus that can apply a controlled and sudden hydrostatic pressure on a film, and record the subsequent film thinning as a function of time. Once the film thickness has reached a stationary value, we test the adhesion between the interfaces of the film by reducing the pressure and measuring the angle between the film and the meniscus. This angle increases on reduction of pressure for adhesive films, which resists the separation of their interfaces. Non-adhesive films separate easily, and the meniscus angle stays constant. At a low microgel concentration, the more densely cross-linked microgels (5 mol% BIS) tend to drain into more adhesive films than the more loosely cross-linked particles (1.5 mol% BIS). The adhesion results from particles that bridge the two air–water interfaces of the film and are shared between them. In these cases, the film, which is initially stabilized by a bilayer of microgel particles, rearrange to a state where the microgels bridge the interfaces. These results are discussed and compared with previous studies at a low concentration of microgels, which have shown that emulsions stabilized with densely cross-linked microgels are more adhesive and less resistant to mechanical stresses than those obtained with lower cross-linking densities. In addition, micron-scale depleted zones with no microgels are observed in the films stabilized with the 5 mol% BIS particles, which eventually lead to the rupture of the films. At 1% wt, the films drain slowly, are not adhesive and have the thickness of a bilayer of microgel; while at 0.1% wt, the films have the thickness of a monolayer of microgel, are adhesive and show bridging. From the thin liquid foam film thicknesses we extract a rough estimation of the radii of adsorbed particles in the thick films before applying the pressure. Our results are consistent with particles being adsorbed in a spread conformation for the 0.1% wt sample and in a compressed conformation for the 1% wt sample. In line with previous studies on emulsions, we conclude that a larger surface coverage may reduce rearrangements, thus preventing bridging.